FAKTOR DETERMINAN KEJADIAN GONDOK DI DAERAH PANTAI JAWA TIMUR - Hafni Bachtiar (Andalas University, Faculty of Public Health, 2009)
The Iodine Deficiency Disorders (IDD) is one of the serious nutritional issues in Indonesia. The survey of IDD in Province of East Java, found that Total Goiter Rate (TGR) in 2003 was higher than 1998 (24.8% and 16.3%) respectively). Iodine deficiency is the main factor of goiter incidence but, there were other factors which could cause the goiter incidence, such as trace element (selenium and zinc) deficiency and exposure of pollutant such as nitrate. The objective of the research is to analyze an association between the trace element andpollutant with the goiter incidence. This research was the cross sectional design, compare goiter and non-goiter respondents. Twenty pupils developing goiter were taken randomly from the goiter population and twenty pupils not suffering of goiter were also taken randomly from the non-goiter population. The median urinary excretion iodine (UEI) levels were higher in the goiter respondents compared with the non-goiter. This might be caused by administration of relatively new iodine capsule to the goiter respondents compared with the non-goiter. The average blood nitrate levels were higher in the in the goiter compared with the non-endemic respondents (575. 75 ± 108.01pg/l :419.45 ± 120.35 pgf I) and there was statistically significant relationship (p < 0.01). According to logistic regression, it can be drawn that the nitrate is determinant factor of coastal area goiter. The goiter prevention program should not be limited to iodine intake, but also include other relevant factors, especially to food and drink nitrate contamination.